Placental Weight in Pregnant Women with Type 1 Diabetes Mellitus: The Association with Fetal Growth - Mehta, Supal; Khoury, Jane; Miodovnik, Menachem; Kawakita, Tetsuya; Ehrlich, Shelley; Bowers, Katherine (American Journal of Perinatology, 2016)
Objective To determine the association between placental weight (PW) and large for gestational age (LGA) in women with type 1 diabetes mellitus (T1DM) and whether glycemic control modifies the association.Study Design In a retrospective analysis of a cohort of women with T1DM, poor glycemic control was defined as glycohemoglobin A1(HbA1)≥ 8.5% (≥2 standard deviations [SD] above mean), and LGA as birth weight > 90th percentile, according to gestation, race, and sex. Multivariable logistic regression was used for analysis. Stratified analyses (HbA1 < 8.5% vs. HbA1 ≥ 8.5%) assessed the role of glycemic control on association between PW and LGA.Results PW in 302 pregnancies was positively associated with LGA (first vs. fourth quartile of PW; odds ratio [OR] = 9.56; 95% confidence interval [CI]: 4.14–22.08). Association varied significantly by glycemic control in the first trimester, but not in the second and third trimesters. For women with first trimester HbA1 concentration < 8.5%, there was no statistically significant association; however, with HbA1 ≥ 8.5%, there was a strong association (OR = 13.40, 95% CI: 3.31, 54.27).Conclusion There was a significant positive association between PW and LGA in infants of women with T1DM, particularly evident in pregnancies with poor glycemic control during the first trimester, highlighting the importance of achieving good glycemic control early in gestation.
Keywords: placental weight; type 1 diabetes mellitus; large for gestational age; glycemic control